Dynamic connectedness between clean energy stock markets and energy commodity markets during times of COVID-19: Empirical evidence from China. (December 2022) - Qi, Haozhi; Ma, Lijun; Peng, Pin; Chen, Hao; Li, Kang
Abstract: We examine the dynamic relationship between clean energy stock markets and energy commodity markets in China from a time-frequency perspective. The daily dataset spans from March 27 th, 2018, to July 29 th, 2022, and is utilized in this study. We find that the clean stock markets are the main contributors and recipients in this dynamic system in the short run, while the solid net contributor role of commodities is detected in the long run. In addition, in most cases, short-term spillovers can dominate the long-run ones. However, during the COVID-19 pandemic, long-term spillovers can dominate short-run spillovers. In particular, it can be seen that in the short run, energy commodities can be easily influenced by clean energy stocks. In the long run, traditional energy assets are less affected. Finally, we show that COVID-19 can increase the hedging effectiveness of the portfolio design. We conclude with policy implications for energy and resources policymakers. Highlights: The clean stock markets are the main contributors and recipients of this dynamic system in the short run. The solid net contributor role of commodities is detected in the long run. In the short run, clean energy stocks can easily influence energy commodities. In the long run, traditional energy assets are less affected. COVID-19 can increase the hedging effectiveness between clean energy stock markets and energy commodity markets.